Bubbles and Crises: The Role of House Prices and Credit - AndreḰ. Anundsen; Frank Hansen; Karsten R. Gerdrup; Kasper Kragh-Sørensen (Norges Bank, 2014)
This paper exploits a quarterly panel data set for 16 OECD countries over the period 1975q1-2013q2 to explore the importance of house prices and credit in affecting the likelihood of a financial crisis. Estimating a set of multivariate logit models, we find that booms in credit to both households and non-financial enterprises are important to account for when evaluating the stability of the financial system. In addition, we find that global housing market developments have predictive power for domestic financial stability. Finally, econometric measures of bubble-like behavior in housing and credit markets enter with positive and highly significant coefficients. Specifically, we find that the probability of a crisis increases markedly when bubble-like behavior coincides with high leverage.
hdl:11250/2495969
Keywords: G01; G18; G21; G28; 330; Basel III; countercyclical capital buffer; early warning models; exuberance indicators; financial market imbalances